Structural design and performance characterization of stable helical auxetic yarns based on the hollow-spindle covering system. Issue 3 (February 2020) - Chen, Junli; Du, Zhaoqun
Helical auxetic yarns (HAYs) spun by ring spinning have a large residual torque, which restricts their application. To address this problem, the hollow-spindle covering system was adopted to prepare structurally stable HAYs consisting of the core yarn and the wrap yarn. Four types of HAYs were manufactured, and a self-designed automatic stretching device was prepared for recording the alteration of yarn diameter. These as-fabricated yarns were measured and characterized in terms of their deformation behavior and auxetic performance. The strain–stress curves of these HAYs have two peaks corresponding to their respective two component yarns during stretch until completely failure, and also it was found that the wrap component is always broken before the core yarn. By comparison, the maximum negative Poisson's ratio (NPR) of −2.55 was achieved with as-prepared HAYs composed of spandex and stainless steel monofilaments. Meanwhile, the structural stability of these yarns was discussed with respect to the residual torque, and the experimental results indicate that the residual torque of these HAYs is obviously smaller than that of conventional ring-spun yarns. These confirm the superiority of our proposed hollow-spindle method. Furthermore, the effects of the diameter of the core yarn and tensile modulus of the wrap yarn on the auxetic behavior were systematically investigated. It is found that a larger NPR can be obtained with a thicker diameter of core yarn and a higher tensile modulus of wrap yarn. It is also demonstrated that an appropriate combination of the component modulus and geometric parameters is essential to fabricate HAY with an obvious auxetic behavior.